Mechanical properties of new-manufactured sandwich composite having carbon fiber core - Kiyak, Burak; Kaman, Mete O. (Sage Publications Ltd, 2019)
In this study, mechanical properties of new-manufactured sandwich composites with various cell structures, having carbon fiber core have been investigated both numerically and experimentally. Three-point bending and compression tests are applied to the specimens as the experimental test approach. Failure behavior and strength of the specimens are extracted as a result of the measurements. The test results also give the opportunity to find out the optimum peak load/density ratio of various core types of sandwich composites. The commercial finite element software ANSYS has been used for numerical analysis. It should be remarked that a good agreement between numerical and experimental results is obtained. The cell shape and height are important parameters on peak load for bending. Additionally, change of cell density is a parameter having effect in same proportion for bending and compression peak loads for these type composites.
Keywords: Sandwich plate; carbon fiber core; finite element analysis; compression; bending